Kegiatan Perlombaan Bulan Muharram Sebagai Motivasi Anak-Anak Di Desa Taba Lagan - Arrizqi, Hasbi; Mubarok, Muhammad Mufti; Andini, Riski; Silvira, Sofi (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Islamic New Year, known as 1 Muharram, is an important event in the Hijri calendar that marks the beginning of the new year for Muslims. This celebration commemorates the migration of the Prophet Muhammad SAW from Mecca to Medina, an event that is not only religiously significant, but also socially and politically. Islamic New Year is a moment of reflection and self-evaluation for Muslims, where they are reminded to increase their worship, strengthen ties of brotherhood, and renew their commitment to carrying out religious teachings. In a modern context, this celebration is also often characterized by social, educational and cultural activities aimed at strengthening Islamic identity amidst the dynamics of global society. Through a deeper understanding of the meaning and value of the Islamic New Year, it is hoped that Muslims can continue to move forward with hope and clear goals. The article was written to find out how effective the Muharram Competition activities are for understanding in depth and increasing religious knowledge. The approach used is to use an educational scientific perspective, especially religious science. The results of this research show that competition activities in the month of Muharram have a significant effect, with children's competitions motivating children and becoming more enthusiastic and interested in studying Islam.